Electronic properties of surface/bulk iodine defects of CsSnBr3perovskite - S. Pramchu (2018)
© 2016 Elsevier B.V. Perovskites are one of a few semiconducting materials that have been shaping the progress of the third generation photovoltaic cells. The power conversion efficiency of the perovskite solar cell has been certified as 20.1% in 2015. In this work, CsSnBr3perovskite has been considered as an alternative material for solar cell applications because of its appropriate band gap. The study has focused on the influence of iodine impurity on the electronic properties of CsSnBr3perovskite modeled on the (001) surface structures. The crystal structures and the electronic properties have been calculated using density functional theory (DFT) within a plane wave pseudopotential framework. The GW method has been also employed to obtain more accurate band gaps. The results show that the iodine defect improves the efficiency of photo absorbance in perovskite solar cell by lowering its energy gap. In particular, the iodine bulk defect in the SnBr2-terminated surface structure was found to exhibit the narrowest band gap. This result suggests that iodine impurity deep into the structure, e.g. iodine-dopant created from high-energy implantation, plays an important role to improve the efficiency of light absorption in CsSnBr3perovskite.